(untitled) (Revista de Ciências Agroveterinárias, 2019)
Water (WL), soil (SL), phosphorus (P) and potassium (K) losses by water erosion and subsurface flow are influenced by soil management and by soil fertilization with swine slurry (SS). The study was conducted between 09/2014 and 11/2015, in a Haplic Dystrudept, to evaluate the 0 (zero), 50, 100 and 200 m³ ha-1 SS doses applied to millet (Pennisetum americanum), black oats (Avena strigosa) and crotalaria (Crotalaria ochroleuca), compared with a soil without cultivation and without SS. The soil total porosity (Tp) and macroporosity (Ma), the P and K concentration in the soil, in the runoff, and in the subsurface flow, the dry mass of the aerial part (DM) of crops, and the WL and SL were determined. The main results show the application of SS in the soil results in an increase in Tp and Ma, as well as in the concentration of P and K in the soil and the DM of the plants, in relation to the absence of SS. Water erosion decreases with an increased dose of SS applied to the soil in the interval between 50 and 200 m3 ha-1. The increase in the dose of SS increases the concentration and total losses of P and K in the runoff and decreases the concentration of these nutrients in the subsurface flow in the interval between 50 and 200 m3 ha-1. The increase of DM of the plants, in the interval between 13.75 and 22.82 t ha-1, decreases SL at an average rate of 2.90 t ha-1. The concentration of K in the subsurface flow water was negatively related to the concentration of the element in the subsurface flow.